The monitoring of pesticides and alkylphenols in selected rivers in the state of Selan Jor, Malaysia - Tan, B.L.L.; Mustafa, A.M. (SAGE Publications, 2004)
Alkylphenols and most pesticides, especially organochlorine pesticides are endocrine-disrupting chemicals and they usually mimic the female hormone, estrogen. Using these chemicals in our environment would eventually lead us to consume them somehow in the food web. Several rivers in the State of Selangor, Malaysia were selected to monitor the level of alkylphenols and pesticides contamination for several months. The compounds were extracted from the water samples using liquid-liquid extraction method with dichloromethane and ethyl acetate as the extracting solvents. The alkylphenols and pesticides were analyzed by selected ion monitoring (SIM) mode using the quadrapole detector in Shimadzu QP-5000 gas chromatograph-mass spectrometer (GCMS). Recovery of most alkylphenols and pesticides were in the range of 50 to 120. Trace amounts of the compounds were detected in the river water samples, mainly in the range of parts per trillion. This technique of monitoring the levels of endocrine-disruptors in river water is consistent and cost effective